Improving Replicability, Reproducibility, And Reliability In Preclinical Research: A Shared Responsibility. (23rd June 2020) - Cheleuitte-Nieves, Christopher; Lipman, Neil S
Abstract: Reproducible and reliable scientific investigation depends on the identification and consideration of various intrinsic and extrinsic factors that may affect the model system used. The impact of these factors must be managed during all phases of a study: planning, execution, and reporting. The value of in vivo (animal) research has come under increasing scrutiny over the past decade because of multiple reports documenting poor translatability to human studies. These failures have been attributed to various causes, including poor study design and execution as well as deficiencies in reporting. It is important to recognize that achieving reproducible and reliable preclinical research results is a joint responsibility that requires a partnership between the investigative team and the animal care and use program staff. The myriad of intrinsic factors, such as species, strain/substrain, age, sex, physiologic and health status, and extrinsic factors, including temperature, humidity, lighting, housing system, and diet, need to be recognized and managed during study planning and execution, as they can influence animal physiology and biological response. Of equal importance is the need to document and report these details. The ARRIVE and PREPARE guidelines were developed by concerned scientists, veterinarians, statisticians, journal editors, and funding agencies to assist investigative teams and scientific journals manage and report on intrinsic and extrinsic factors to improve reproducibility and reliability. This issue of the ILAR Journal will focus on the various extrinsic factors that have been recognized to confound animal research.